RIBA PERSPEKTIF SEJARAH DAN RELIGIUSITAS - Sapriadi; Karina Alifiana Karunia; St. Hadijah Wahid (Institut Agama Islam Muhammadiyah Sinjai, 2020)
Eksistensi riba telah dikaji baik dalam tataran dunia akademik maupun pada kitab-kitab klasik. Akan tetapi, hingga saat ini praktik riba masih terjadi diberbagai aktivitas, baik dalam jual beli, hutang piutang, maupun transaksi-transaksi lainnya. Pandangan Islam, riba tidak hanya dipandang sebagai hal yang haram untuk dilakukan, akan tetapi merupakan perbuatan yang tidak memiliki moralitas bagi pelaku riba. Pelarangan melakukan praktik riba tidak hanya terjadi pada masa Islam, melainkan sebelum Islam agama lain seperti Yahudi dan Nasrani juga melarang pengambilan riba. Dengan demikian, riba membutuhkan penelaran konsep riba dari kitab-kitab klasik dari segi sejarah, konsep maupun legalitas hukum riba. The existence of usury has been studied both in the academic world and in classical books. However, until now the practice of usury still occurs in various activities, both in buying and selling, accounts payable, and other transactions. Thus, usury requires special learning. This research is a quantitative type of research, while the specification of this research is descriptive analytical, namely research that explains the situation that occurs, with the aim of bringing out facts, followed by analysis, aiming to find answers to the problem of usury. The collection of legal materials in this writing is done by conducting library research and document studies. The main approach taken is interpretation (historical and religious). Based on the results of the research conducted by the author, it can be concluded that in the Islamic view, usury is not only seen as an unlawful thing to do, but is an act that has no morality for the perpetrator of usury. The prohibition of practicing usury did not only occur during the Islamic era, but before Islam, other religions such as Judaism and Christianity also prohibited the taking of usury. Broadly speaking, usury is grouped into two, namely: usury due to accounts payable and usury due to buying and selling.